Enhancing ambient and elevated temperature performance of hypoeutectic Al–Ce cast alloys by Al3(Sc,Zr) precipitate - Abid Abdu Mohammed; Suwaree Chankitmunkong; Shihao Wang; Dmitry Eskin; Ussadawut Patakham; Chaowalit Limmaneevichitr; Phromphong Pandee (Journal of Materials Research and Technology, 2023)
This study explored the consequences of incorporating Sc and Zr into hypoeutectic Al–9Ce cast alloys, specifically investigating their influence on microstructure and mechanical properties. The findings demonstrate the significant reduction in the grain size of the Al–9Ce alloy while successfully maintaining the distinctive shape of the eutectic Al11Ce3 phase through the incorporation of Sc and Zr additions. During aging treatments, Al3(Sc,Zr) coherent precipitates formed both at the interface between the α-Al and Al11Ce3 phases and within the α-Al matrix. Remarkably, this leads to optimal hardness achieved within a short duration of 3 h at 350 °C. Peak-aged quaternary Al–9Ce-xSc-yZr alloys show significantly better tensile strength than the binary Al–Ce alloy in both ambient and elevated temperatures. Overall, the study underscores promising prospects of Al–Ce-Sc-Zr alloys for use in high-temperature applications, as they exhibit enhanced mechanical properties.
Keywords: Aluminum Alloy Microstructure Properties; Aluminum Alloys Composites Properties; Microstructure and mechanical properties